Rancang Bangun Sistem Informasi Rekam Medis Berbasis Web Pada Klinik H2LC Surabaya - Pratiwi, Maria Sherly Jevita; Arifin, Mochammad; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Clinic House of Healthy Living Center (H2LC) is a clinic Aesthetic & Anti Aging consistently apply the concept of healthy living by combining elements of beauty and health of the skin and body. Constraints faced H2LC Clinic is the start of record-keeping, duplication of card history data medical records of patients, health progress / results of treatment patients were still recorded on medical record cards, prescriptions that are difficult to read, and payments are still using hand-written memorandum.To overcome the above problems the development method used in Information Systems Web-Based Medical Record On H2LC Clinic Surabaya is to use the System Development Life Cycle (SDLC) waterfall. Medical record system electronically application is beneficial not only administratively. But can be felt doctors and health workers is the ease in accessing patient information that ultimately helps in clinical needs.The results based on the implementation and evaluation of the banks have done the research was able to make Medical Record Information System Web-Based Clinical H2LC In Surabaya that produce information and manage the registration process assessment of the patient, record-keeping, and payments. Generate reports to consider the development of patient medical record information to be more easily and quickly.